2016
DOI: 10.3758/s13415-016-0481-9
|View full text |Cite
|
Sign up to set email alerts
|

Facial identity and emotional expression as predictors during economic decisions

Abstract: Two of the sources of information most relevant to guide social decisionmaking are the cooperative tendencies associated to different people and their facial emotional displays. The present electrophysiological experiment aimed to study how the use of personal identity and emotional expressions as cues impacts different stages of face processing and their potential isolated or interactive processing. Participants played a modified Trust Game with 8 different alleged partners, and in separate blocks either the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 100 publications
(206 reference statements)
0
9
0
Order By: Relevance
“…For instance, the multi-stage account of facial expression recognition proposed that the N170 reflects the stage of distinguishing emotional and neutral expressions ( Luo et al, 2010 ; Zhang et al, 2013 ; Calvo and Nummenmaa, 2016 ). Furthermore, the N170 was shown to be modulated by valence ( Hietanen and Astikainen, 2013 ; Alguacil et al, 2017 ). For example, Hietanen and Astikainen (2013) used an affective priming paradigm and found that the amplitude of N170 elicited by neutral faces was affected by the valence of primes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the multi-stage account of facial expression recognition proposed that the N170 reflects the stage of distinguishing emotional and neutral expressions ( Luo et al, 2010 ; Zhang et al, 2013 ; Calvo and Nummenmaa, 2016 ). Furthermore, the N170 was shown to be modulated by valence ( Hietanen and Astikainen, 2013 ; Alguacil et al, 2017 ). For example, Hietanen and Astikainen (2013) used an affective priming paradigm and found that the amplitude of N170 elicited by neutral faces was affected by the valence of primes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ERP studies have produced ambiguous results on the time course of valence processing. Some have found that the P1, N1 and P2 components can be modulated by emotional valence ( Smith et al, 2003 ; Huang and Luo, 2006 ; Lithari et al, 2010 ; Zhang et al, 2013 ; Alguacil et al, 2017 ). However, other studies have shown that valence can also affect later components, such as LPP ( Bernat et al, 2001 ; Schupp et al, 2004 ), P3 ( Huang and Luo, 2006 ; Lithari et al, 2010 ; Alguacil et al, 2017 ), and LPC ( Huang and Luo, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, rational decision-making based on risk attitudes is not sufficient to explain how we decide to place our trust in someone. Indeed, several social factors such as socioeconomic status (e.g., Blue et al, 2018 ; Bogliacino et al, 2018 ), emotion (e.g., Tortosa et al, 2013b ; Alguacil et al, 2017 ), or face appearance (e.g., van ’t Wout and Sanfey, 2008 ; Li et al, 2017 ) have been shown to affect trust decision-making at zero acquaintance. All the social variables (e.g., facial expression, gaze direction, gender, ethnicity, attractiveness) that might influence the impression formation process ( Uleman and Kressel, 2013 ; Stolier and Freeman, 2016 ) can in turn affect the decisions being made.…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes of many decisions in the social domain depend on the behavior of others and we need to form expectations to adjust our behavior accordingly. For this reason, we often gather information not only about our interaction partners’ identity or emotional state 3 , 5 , 8 , 9 , but also about the process through which they make decisions 7 , 10 13 .…”
Section: Introductionmentioning
confidence: 99%